Environment-friendly anti-deformation reed-wood composite shaving board and preparation method thereof

By using specific components for directional application and formaldehyde-free adhesives in furniture boards, the problems of environmental protection and easy deformation of the boards are solved, achieving high strength, low formaldehyde release, and stability.

CN119550447BActive Publication Date: 2025-11-18NIELKODA (TIELING) HIGH-TECH MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411715318.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-11-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing furniture boards have environmental problems and are prone to deformation, especially with excessive formaldehyde release and poor mechanical properties, leading to safety hazards and instability in use.

Method used

Environmentally friendly, deformation-resistant reed-wood composite particleboard is prepared by directional laying of wood chips, reed fibers, basalt fibers, lignin fibers, plant extracts, etc., combined with formaldehyde-free adhesives and specific polymers, and through directional hot pressing, improving internal bond strength and waterproof performance.

Benefits of technology

It effectively reduces formaldehyde release, improves the crack resistance and deformation resistance of the board, enhances static bending strength and screw holding force, and ensures the stability and environmental friendliness of the board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156754470000191
    Figure BDA0005156754470000191
  • Figure BDA0005156754470000201
    Figure BDA0005156754470000201
  • Figure BDA0005156754470000211
    Figure BDA0005156754470000211
Patent Text Reader

Abstract

The application discloses an environment-friendly anti-deformation reed-wood composite shaving board and a preparation method thereof, belongs to the technical field of the board material, and the raw material of the reed-wood composite shaving board comprises wood chips, reed fibers, basalt fibers, lignin fibers, plant extracts, nano silicon dioxide, acetylated di-starch phosphate, C30-45 alkyl cetyl stearyl dimethicone cross-linked polymer, PEG-10 polydimethylsiloxane-vinyl dimethicone cross-linked polymer, methyl methacrylate cross-linked polymer, MDI adhesive and organic silicon waterproof agent in specific proportions. The components are used in cooperation, the shaving board is prepared in a directional mode, has excellent mechanical properties, is resistant to cracking and deformation, and is improved in the environmental protection performance, and the usage amount of glue is reduced. The novel formaldehyde-free adhesive and the plant extracts are adopted to replace traditional formaldehyde-containing glue and mold-proof and insect-proof agents, formaldehyde release is effectively avoided, and a healthier home decoration board selection is provided for consumers.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of board materials, and particularly relates to an environmentally-friendly anti-deformation reed-wood composite shaving board and a preparation method thereof. BACKGROUND

[0002] In the field of furniture manufacturing, the selection and application of board materials have always been a crucial link. With the improvement of people's living standards and the increasing demand for home environment, furniture board technology has undergone a long development and change.

[0003] In the early days, solid wood was the main material for furniture production. Solid wood has natural texture and texture, giving people a simple and high-end feeling. However, solid wood resources are limited, with a long growth cycle, and as large-scale exploitation and utilization, high-quality solid wood becomes increasingly scarce, and the cost continues to rise. This prompted people to begin to explore other alternative board materials. Thus, man-made board materials emerged. Fiberboard is one of the earliest man-made board materials, which is made by separating, gluing, laying, and hot pressing wood fibers or other plant fibers. Fiberboard has the advantages of uniform material, small difference in strength in vertical and horizontal directions, etc., but its internal structure is relatively loose, and it is easy to absorb moisture and swell in a humid environment, leading to deformation, strength reduction, and other problems. Plywood is made by gluing multiple veneers together, and the fiber direction of adjacent veneers is perpendicular to each other, which improves the anisotropy of wood to some extent and has high strength and stability. However, plywood relies heavily on glue during production, and if the glue quality is poor or used improperly, it can easily release harmful substances such as formaldehyde, which is harmful to human health. Shaving board is also a commonly used furniture board, which is made by pressing wood chips with glue. Shaving board has relatively low cost and good sound absorption and heat insulation performance, but due to its granular structure, the surface flatness is poor, and additional surface treatment process is required when making fine furniture, and there is also the risk of formaldehyde release.

[0004] At present, there are various types of board materials with uneven product quality, and furniture board materials generally have the following problems:

[0005] (1) Environmental problem: the use of inferior adhesive or excessive use of adhesive leads to excessive formaldehyde release, which is harmful to human health.

[0006] (2) Quality problem: due to the material properties of the board, the mechanical properties such as static bending strength and screw holding force are poor, and bending deformation, fracture, and other problems easily occur during use, which poses a safety hazard. Factors such as board density, moisture content, and water resistance cause the board to gradually deform over time, affecting the appearance and use of furniture. SUMMARY

[0007] In the prior art, the quality of plate products is uneven, and furniture plates generally still have poor environmental protection and easy deformation problems. The present application provides an environmentally friendly anti-deformation reed wood composite shaving board and a preparation method thereof, which uses wood chips and reed and other components for directional paving, improves the strength and stability of the plate, and has improved environmental performance, reducing the amount of glue used. By using a new type of formaldehyde-free adhesive and plant extract to replace traditional formaldehyde-containing glue and mold and insect repellents, the release of formaldehyde is effectively avoided, providing consumers with a healthier furniture option. The specific technical scheme is as follows:

[0008] An environmentally friendly anti-deformation reed wood composite shaving board, the reed wood composite shaving board comprises the following raw materials in mass fraction: wood chips 60-70 parts, reed fibers 50-60 parts, basalt fibers 5-10 parts, lignin fibers 2-5 parts, plant extracts 0.5-1 parts, nano silicon dioxide 2-5 parts, acetylated di-starch phosphate 1-4 parts, C30-45 alkyl cetyl stearyl dimethicone cross-linked polymer 2-5 parts, PEG-10 polydimethylsiloxane-vinyl dimethicone cross-linked polymer 1-3 parts, methyl methacrylate cross-linked polymer 3-6 parts, MDI adhesive 6-8 parts, silicone waterproof agent 0.5-1 parts.

[0009] In the above technical solution, the wood chips are oak tree trunk wood chips.

[0010] In the above technical solution, the wood chips have a length range of 5-8 cm, a width range of 0.5-2 cm, and a thickness range of 0.2-0.5 cm.

[0011] In the above technical solution, the reed fibers have a length range of 2-4 cm, a width range of 0.1-0.5 cm, and a thickness range of 0.1-0.3 cm.

[0012] In the above technical solution, the basalt fibers have a length range of 0.3-0.8 cm and a diameter range of 5-15 μm.

[0013] In the above technical solution, the lignin fibers are flocculent lignin fibers, and the flocculent lignin fibers have a length range of 0.6 cm or less.

[0014] In the above technical solution, the nano silicon dioxide has a particle size range of 300 nm or less.

[0015] In the above technical solution, the acetylated di-starch phosphate has a particle size of less than 250 mesh.

[0016] In the above technical solution, the methyl methacrylate cross-linked polymer has a particle size of less than 250 mesh.

[0017] The preparation method of the plant extract includes the following steps: mixing whole plants of wormwood, achyrophorus, Raoulia petraea and rosemary according to a mass ratio of wormwood: achyrophorus: Raoulia petraea: rosemary = (5-10):(5-10):(5-10):(1-5), crushing to obtain a crushed product, then performing percolation with 8-10 times the mass of the crushed product of ethanol to obtain an extraction solution, evaporating the ethanol, drying and breaking to obtain the plant extract.

[0018] The preparation method of the environment-friendly anti-deformation reed-wood composite shaving board includes the following steps:

[0019] S1, reed fiber treatment:

[0020] The reed fiber is placed in a soaking pool and soaked with a sodium hydroxide aqueous solution, and after soaking, the sodium hydroxide aqueous solution is filtered out, the reed fiber is washed with clean water until neutral, dried, and the water content is controlled at 8%-12% to obtain purified reed fiber;

[0021] S2, wood chip treatment:

[0022] The wood chip is placed in a steam treatment tank and treated in saturated steam at 180-200 DEG C and a pressure of 0.8-1.2 MPa for 5-10 min to improve the flexibility and plasticity of the wood chip, and the water content of the treated wood chip is controlled at 6%-10% to obtain softened wood chip;

[0023] S3, premixing treatment:

[0024] The basalt fiber, nano-silicon dioxide, acetylated dextrin phosphate, and methyl methacrylate cross-linked polymer are first airflow mixed, then the lignin fiber is added and second airflow mixed to obtain a mixture A;

[0025] S4, glue mixing:

[0026] The purified reed fiber, softened wood chip, and plant extract are added to a glue mixer and stirred at 300-500 r / min for 2-3 min to mix uniformly; then the mixture A is added and stirred at 600-700 r / min for 5-8 min to mix uniformly; then the MDI adhesive and PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane cross-linked polymer are sequentially added under stirring, and stirred at 600-700 r / min for 5-8 min to mix uniformly; then the C30-45 alkyl cetyl stearyl polydimethylsiloxane cross-linked polymer and silicone waterproof agent are sequentially added under stirring, and stirred at 500-600 r / min for 3-5 min to mix uniformly to obtain a base material;

[0027] S5, paving and orientation:

[0028] The base material is paved by a paving device, the paving thickness is controlled at 1cm-5cm, a mechanical orientation device is used to arrange the long axis direction of the softened wood chips at an angle of 45°-60° with the length direction of the board to improve the mechanical properties of the board, and other components are evenly distributed and filled between the softened wood chips to obtain a paved and oriented board blank;

[0029] S6, hot pressing:

[0030] The paved and oriented board blank is sent into a continuous flat pressing hot press for continuous hot pressing: the hot pressing speed is 350mm / s-580mm / s, the hot pressing factor is 3.3s / mm-4.5s / mm, and the hot medium is heat conducting oil; after continuous hot pressing, a hot pressed board is obtained;

[0031] S7, post-processing:

[0032] The hot pressed board is cooled by natural cooling or air cooling to reduce the temperature of the board to room temperature; then the board is edge cut and sanded to make the board size accurate and the surface flat, and a reed wood composite particle board is obtained.

[0033] In S1 of the above preparation method, the concentration of the sodium hydroxide aqueous solution is 1wt%-2wt%, the soaking time is 2h-3h, and the soaking temperature is controlled at 40℃-50℃.

[0034] In S3 of the above preparation method, the parameters of the first airflow mixing are: airflow speed 10m / s-20m / s, pressure 0.4MPa-0.6MPa, and mixing time 10min-15min; the parameters of the second airflow mixing are: airflow speed 8m / s-15m / s, pressure 0.3MPa-0.5MPa, and mixing time 5min-10min.

[0035] In S6 of the above preparation method, the continuous flat pressing hot press is divided into five zones from front to back, respectively, zone one, zone two, zone three, zone four and zone five, and the pressure and temperature settings of each zone are:

[0036] Zone one: system 1: 90±5N / cm 2 , system 2: 280±5N / cm 2 , temperature 235±5℃;

[0037] Zone two: system 3: 420±5N / cm 2 , system 4: 450±5N / cm 2 , system 5: 375±5N / cm 2 , system 6: 335±5N / cm2 System 7: 280 ± 5 N / cm 2 System 8: 240 ± 5 N / cm 2 System 9: 210 ± 5 N / cm 2 Temperature 235 ± 5℃;

[0038] Three zones: System 10: 150 ± 5 N / cm 2 System 11: 140 ± 5 N / cm 2 System 12: 130 ± 5 N / cm 2 Temperature 230 ± 5℃;

[0039] Four zones: System 13: 90 ± 5 N / cm 2 System 14: 130 ± 5 N / cm 2 System 15: 130 ± 5 N / cm 2 System 16: 90 ± 5 N / cm 2 System 17: 130 ± 5 N / cm 2 System 18: 130 ± 5 N / cm 2 System 19: 130 ± 5 N / cm 2 System 20: 130 ± 5 N / cm 2 Temperature 200 ± 5℃;

[0040] Five zones: System 21: 50 ± 5 N / cm 2 Temperature 190 ± 5℃.

[0041] The reed wood composite shaving board provided by the application has the advantages that:

[0042] First, the raw materials of the reed wood composite shaving board of the application include wood chips, reed fibers, basalt fibers, lignin fibers, plant extracts, nano silicon dioxide, acetylated di-starch phosphate, C30-45 alkyl cetyl stearyl dimethicone cross-linked polymer, PEG-10 dimethicone-vinyl dimethicone cross-linked polymer, methyl methacrylate cross-linked polymer, MDI adhesive, and silicone waterproof agent, and each component is used in combination to prepare the shaving board in a directional manner, so that the shaving board has excellent mechanical properties, is resistant to cracking and deformation, and is safe and environmentally friendly.

[0043] Wood chips and reed fibers are the main structural materials of the board, providing basic strength support. The production cycle of oak is long, the tree density is large, the hardness is high, and the waterproof performance is good, so it is not easy to deform when made into a board. Reed, as an aquatic plant, has a layer of biological wax on its surface, which has strong waterproof properties. The long fibers of wood chips and reed fibers interweave with each other, increasing the internal friction of the board, which helps to improve the static bending strength, internal bonding strength, and screw holding force, and reduce the water absorption and swelling deformation rate.

[0044] Basalt fibers have high strength and modulus, which can enhance the overall strength of the board and play a positive role in static bending strength and crack resistance. Like in composite materials, they act as reinforcing skeletons, preventing crack propagation.

[0045] Lignin fibers can fill the gaps between other materials, enhancing the bonding force between materials, improving internal bonding strength, and to some extent, improving crack resistance. Its flocculent structure can effectively lock other ingredients.

[0046] Plant extracts mainly play a role in preventing mold and insects, and have little effect on the mechanical properties of the board, but they can help extend the service life of the board and maintain the structural integrity and safety of the board.

[0047] Nano-silicon dioxide can fill the tiny pores of the material, improving the density of the material and thus reducing water absorption and swelling deformation, while also enhancing the hardness of the material and improving the static bending strength and internal bonding strength.

[0048] Acetylated distarch phosphate plays a bonding role, enhancing the bonding force between ingredients, improving internal bonding strength and screw holding force, and good adhesion can also reduce water absorption.

[0049] C30-45 alkyl cetyl stearyl dimethicone cross-linked polymer and PEG-10 dimethicone-vinyl dimethicone cross-linked polymer can improve the surface properties of the board, improve the waterproof performance, and reduce the water absorption and swelling deformation rate. At the same time, it also helps to disperse and bond the ingredients, indirectly improving the mechanical properties of the board; PEG-10 dimethicone-vinyl dimethicone cross-linked polymer has adhesion-promoting effect on MDI adhesive, good adhesion, can reduce water absorption, and has anti-swelling deformation.

[0050] Methyl methacrylate cross-linked polymer can enhance the cross-linking degree between materials, improve internal bonding strength and crack resistance, and also help to reduce water absorption and swelling deformation rate.

[0051] MDI adhesive as the main adhesive, various components are closely bonded together, significantly improve the inner bonding strength, holding screw force and crack resistance, and MDI adhesive is formaldehyde-free, environmentally friendly, and MDI adhesive itself also has good waterproofness. The organic silicon waterproof agent forms a waterproof layer on the surface of the plate, reduces the water absorption and swelling deformation rate, and improves the moisture resistance of the plate.

[0052] Second, basalt fibers provide high-strength reinforcement, bearing a large stress when subjected to external forces, preventing large deformation and cracking of the plate. Lignin fibers fill the gaps between basalt fibers and other materials, on the one hand, making the basalt fibers more evenly distributed in the plate, and on the other hand, enhancing the connection between the components. The synergy of the two can effectively improve the static bending strength and crack resistance, and the filling and bonding of lignin fibers further enhance the inner bonding strength.

[0053] Third, nano-silica fills the tiny pores, making the plate structure more dense. Methyl methacrylate cross-linked polymer forms a cross-linked network between materials, tightly connecting each component. The filling of nano-silica can provide better attachment sites for cross-linked polymers, enhancing cross-linking effects. The synergistic effect of the two helps to reduce water absorption and swelling deformation rate, while improving the inner bonding strength and static bending strength, as a more dense structure and good cross-linking can better resist external forces and water intrusion.

[0054] Fourth, C30-45 alkyl cetyl stearyl dimethicone cross-linked polymer and PEG-10 dimethicone-vinyl dimethicone cross-linked polymer, both of which help to improve the waterproofness and gum flexibility of the plate. C30-45 alkyl cetyl stearyl dimethicone cross-linked polymer mainly acts on the surface and interior of the plate, forming a waterproof barrier; PEG-10 dimethicone-vinyl dimethicone cross-linked polymer enhances the waterproof connection between components inside the material. They work together to more effectively reduce water absorption and swelling deformation rate, while working together during material dispersion and bonding to improve flexibility, balance the hardness of pure MDI glue, and prevent the plate from cracking, ensuring the overall performance stability of the plate.

[0055] Five, nano-silica fills the pores, methyl methacrylate cross-linked polymer strengthens cross-linking, C30-45 alkyl cetearyl dimethicone cross-linked polymer and PEG-10 dimethicone-vinyl dimethicone cross-linked polymer enhance waterproof performance. They work together to make the internal structure of the board more compact, cross-linking more complete, and waterproof performance better. In terms of improving static bending strength and internal bonding strength, the compact structure and good cross-linking can effectively resist external force; in terms of reducing water absorption swelling deformation rate, the combination of nano-silica filling and waterproof polymer forms a comprehensive waterproof barrier to prevent water from entering and causing swelling deformation.

[0056] Six, in the preparation method, reed fiber treatment: through sodium hydroxide soaking and cleaning and drying, remove impurities in reed fiber, improve the surface performance of the fiber, make it easier to combine with other ingredients, and appropriate moisture content helps to maintain the performance of the fiber in subsequent processing.

[0057] Seven, in the preparation method, wood chip treatment: steam treatment makes the wood chip soft and plasticity enhanced, making it easier to arrange according to requirements during paving and orientation, so that the long axis direction of the wood chip is arranged at a certain angle to the length direction of the board. This arrangement can effectively improve the mechanical properties of the board, and the appropriate moisture content after treatment is beneficial to the bonding with other ingredients.

[0058] Eight, in the preparation method, premixing treatment: airflow mixing makes various powdered and fibrous additives (such as basalt fiber, nano-silica, etc.) uniformly mixed to form mixture A. Uniform mixing ensures that each additive is evenly distributed in the board, fully exerting its reinforcing, filling, and bonding effects, thereby improving static bending strength, internal bonding strength, and crack resistance, and reducing water absorption swelling deformation rate.

[0059] Nine, in the preparation method, glue mixing: by gradually adding raw materials and stirring, each ingredient is fully mixed and bonded under the action of the adhesive. The appropriate stirring speed and time ensure good bonding between purified reed fiber, softened wood chip, plant extract, mixture A, and various adhesives and polymers, improving internal bonding strength, screw holding force, and crack resistance. The sequential MDI adhesive and PEG-10 dimethicone-vinyl dimethicone cross-linked polymer can exert the adhesion of PEG-10 dimethicone-vinyl dimethicone cross-linked polymer to MDI adhesive. After the MDI adhesive fully infiltrates the substrate, the PEG-10 dimethicone-vinyl dimethicone cross-linked polymer has a further consolidation and adhesion effect, improving the bonding and toughness of the system and reducing the likelihood of cracking.

[0060] X. In the preparation method, the softwood chips are arranged at a specific angle by paving and mechanical orientation at a certain thickness, which is the preparation technology of oriented shaving board, and can significantly improve the static bending strength and crack resistance. Other components are evenly distributed between the wood chips to ensure the uniformity of the board structure, which also helps to improve the internal bonding strength and reduce the swelling deformation rate. The hot pressing process further compacts the board under high temperature and pressure, enhancing the bonding between the components. Proper heating rate, hot pressing temperature, pressure and hot pressing time can ensure the quality of the board, and the control of the unloading rate can also help to prevent cracks and other defects in the board during unloading, improving the crack resistance.

[0061] XI. In the preparation method, specific hot pressing parameters are designed. The high pressure in the initial stage of the second zone can make the shavings tightly bond during the initial forming stage of the board. In the high temperature environment, the wood fibers in the shavings are softened, and the high pressure promotes the interweaving and embedding of the fibers, just like weaving loose threads into a tight cloth under pressure, so that the board can withstand greater bending force during subsequent use, improving the static bending strength, and improving the internal bonding strength, screw holding force and crack resistance. The pressure gradually decreases from zone one to zone five, and this gradual pressure setting helps to stabilize the structure of the board. After the initial formation of a tight structure under high pressure in the early stage, the gradually decreasing pressure in the subsequent process allows the board to slowly adjust its internal structure during hot pressing, reducing internal stress concentration. When subjected to bending force, the stress distribution in the board is more uniform, avoiding local overloading and further enhancing the static bending strength. With the advancement of the hot pressing area, the combination of shavings inside the board becomes more firm. The temperature in the third zone is slightly reduced, but the pressure is still maintained, and then the pressure and temperature in the fourth and fifth zones are adjusted. This gradual hot pressing process allows the shavings board to form good internal bonding at different levels, and even if subjected to a force perpendicular to the surface of the board during use, it is not easy to delaminate, ensuring the internal bonding strength. The appropriate pressure in the fourth and fifth zones maintains the stability of the board structure, and the internal structure of the board will not be loose due to sudden pressure drop. When external force acts on the screw during use, the board can provide stable counterforce to ensure that the screw does not loosen easily, effectively improving the screw holding force. From zone one to zone five, the temperature and pressure change in a gradient, which allows the internal stress of the board to gradually release during hot pressing. When the board is subjected to external force impact or deformation due to environmental factors, its internal structure has already undergone reasonable stress adjustment during the hot pressing process, and can better resist the generation of cracks.

[0062] In summary, the reed wood combined oriented strand board improves the strength and stability of the board, and has improved environmental performance, and reduces the amount of glue used. By using a new type of formaldehyde-free adhesive and plant extract to replace traditional formaldehyde-containing glue and mold-proof insect repellent, the release of formaldehyde is effectively avoided, providing consumers with a healthier furniture choice. DETAILED DESCRIPTION

[0063] The application will be further described below in conjunction with specific implementation cases, but the application is not limited to these examples.

[0064] Example 1

[0065] An environmentally friendly anti-deformation reed wood composite strand board, the reed wood composite strand board comprises the following raw materials in mass fraction: wood chips 60 parts, reed fibers 60 parts, basalt fibers 8 parts, lignin fibers 3.5 parts, plant extract 0.8 parts, nano silicon dioxide 3 parts, acetylated di-starch phosphate 2.5 parts, C30-45 alkyl cetyl stearyl dimethicone cross-linked polymer 4 parts, PEG-10 dimethicone-vinyl dimethicone cross-linked polymer 2 parts, methyl methacrylate cross-linked polymer 5 parts, MDI adhesive 7 parts, silicone waterproof agent 0.6 parts.

[0066] The wood chips are oak tree trunk chips. The specifications of the wood chips are: length range of 5cm-8cm, width range of 0.5cm-2cm, and thickness range of 0.2cm-0.5cm. The specifications of the reed fibers are: length range of 2cm-4cm, width range of 0.1cm-0.5cm, and thickness range of 0.1cm-0.3cm. The specifications of the basalt fibers are: length range of 0.3cm-0.8cm, and diameter range of 5um-15um. The lignin fibers are flocculent lignin fibers, and the length range of the flocculent lignin fibers is 0.6cm or less. The particle size range of the nano silicon dioxide is 300nm or less. The particle size of the acetylated di-starch phosphate is below 250 mesh. The particle size of the methyl methacrylate cross-linked polymer is below 250 mesh.

[0067] The preparation method of the plant extract comprises the following steps: mixing whole plants of mugwort, white chrysanthemum, purple coneflower and rosemary according to a mass ratio of 8:6:8:3, crushing to obtain a crushed product, then performing percolation on the crushed product with 9 times the mass of ethanol to obtain a leaching solution, evaporating the ethanol, drying and scattering to obtain the plant extract.

[0068] The preparation method of the above-mentioned environmentally friendly anti-deformation reed wood composite strand board comprises the following steps:

[0069] S1, reed fiber treatment:

[0070] Put the reed fibers into the soaking pool, soak for 2.5h with 1.5wt% sodium hydroxide solution, control the soaking temperature at 45℃, filter out the sodium hydroxide solution after soaking, take the reed fibers and wash to neutral with water, dry to control the water content at 10%, get the purified reed fibers;

[0071] S2: Wood chip treatment:

[0072] Put the wood chips into the steam treatment tank, treat for 8min in the saturated steam at 190℃ and 1.0MPa air pressure, to improve the flexibility and plasticity of the wood chips, control the water content of the treated wood chips at 8%, get the softened wood chips;

[0073] S3, premixing treatment:

[0074] Firstly, mix basalt fibers, nano-silicon dioxide, acetylated dextrin phosphate, and methyl methacrylate cross-linked polymer by airflow mixing, parameters: airflow speed 15m / s, pressure 0.5MPa, mixing time 12min; then add lignin fibers, and mix by airflow mixing for the second time, parameters: airflow speed 12m / s, pressure 0.4MPa, mixing time 8min; get mixture A;

[0075] S4, glue mixing:

[0076] Put the purified reed fibers, softened wood chips, and plant extracts into the glue mixer, stir at 400r / min for 2min, mix evenly; then add mixture A, stir at 650r / min for 6min, mix evenly; then add MDI adhesive and PEG-10 dimethicone-vinyl dimethicone cross-linked polymer in turn under stirring, stir at 650r / min for 7min, mix evenly; then add C30-45 alkyl cetyl stearyl dimethicone cross-linked polymer and silicone waterproof agent in turn under stirring, stir at 550r / min for 4min, mix evenly, get the base material;

[0077] S5, paving and orientation:

[0078] Pave the base material through the paving equipment, according to the thickness requirement, implement 1cm, 1.5cm, 2cm, 2.5cm, 3cm, 5cm paving thickness respectively, use mechanical orientation device to arrange the long axis direction of the softened wood chips at 50° angle with the length direction of the board, to improve the mechanical properties of the board, other components are evenly distributed and filled between the softened wood chips, get the paved and oriented board blank;

[0079] S6, hot pressing:

[0080] The oriented board is sent into a continuous flat pressing hot press for continuous hot pressing: the hot pressing speed is 460 mm / s, the hot pressing factor is 3.8 s / mm, and the hot medium is heat conducting oil; the continuous flat pressing hot press is divided into five zones from front to back, namely zone 1, zone 2, zone 3, zone 4 and zone 5, and the pressure and temperature of each zone are set as follows:

[0081] Zone 1: system 1: 90 N / cm 2 , system 2: 280 N / cm 2 , temperature 235℃;

[0082] Zone 2: system 3: 420 N / cm 2 , system 4: 450 N / cm 2 , system 5: 375 N / cm 2 , system 6: 335 N / cm 2 , system 7: 280 N / cm 2 , system 8: 240 N / cm 2 , system 9: 210 N / cm 2 , temperature 235℃;

[0083] Zone 3: system 10: 150 N / cm 2 , system 11: 140 N / cm 2 , system 12: 130 N / cm 2 , temperature 230℃;

[0084] Zone 4: system 13: 90 N / cm 2 , system 14: 130 N / cm 2 , system 15: 130 N / cm 2 , system 16: 90 N / cm 2 , system 17: 130 N / cm 2 , system 18: 130 N / cm 2 , system 19: 130 N / cm 2 , system 20: 130 N / cm 2 , temperature 200℃;

[0085] Zone 5: system 21: 50 N / cm 2 , temperature 190℃.

[0086] After continuous hot pressing, the hot-pressed board is obtained;

[0087] S7, post-processing:

[0088] The hot-pressed board is cooled by natural cooling to room temperature, and then the board is edge cut and sanded to make the board size accurate and the surface flat, and different thicknesses of reed wood composite particle boards are obtained.

[0089] The reed-wood composite shaving board with a paving thickness of 1.5 cm is selected as the test sample.

[0090] Embodiment 2

[0091] The reed-wood composite shaving board includes the following raw materials in mass fractions: wood chips 65 parts, reed fibers 55 parts, basalt fibers 5 parts, lignin fibers 2 parts, plant extract 0.5 parts, nano silicon dioxide 2 parts, acetylated di-starch phosphate 1 part, C30-45 alkyl cetyl stearyl dimethicone cross-linked polymer 2 parts, PEG-10 dimethicone-vinyl dimethicone cross-linked polymer 1 part, methyl methacrylate cross-linked polymer 3 parts, MDI adhesive 6 parts, and silicone waterproof agent 0.5 parts.

[0092] The wood chips are oak tree trunk wood chips. The wood chips have a length range of 5 cm to 8 cm, a width range of 0.5 cm to 2 cm, and a thickness range of 0.2 cm to 0.5 cm. The reed fibers have a length range of 2 cm to 4 cm, a width range of 0.1 cm to 0.5 cm, and a thickness range of 0.1 cm to 0.3 cm. The basalt fibers have a length range of 0.3 cm to 0.8 cm and a diameter range of 5 μm to 15 μm. The lignin fibers are flocculent lignin fibers, and the flocculent lignin fibers have a length range of 0.6 cm or less. The nano silicon dioxide has a particle size range of 300 nm or less. The acetylated di-starch phosphate has a particle size of less than 250 mesh. The methyl methacrylate cross-linked polymer has a particle size of less than 250 mesh.

[0093] The preparation method of the plant extract includes the following steps: mixing whole plants of mugwort, achyrophorus, purple coneflower, and rosemary according to a mass ratio of 5:5:5:1, crushing the whole plants to obtain crushed materials, performing percolation on the crushed materials with 8 times the mass of ethanol to obtain a leaching solution, evaporating the ethanol, drying and scattering to obtain the plant extract.

[0094] The preparation method of the reed-wood composite shaving board includes the following steps:

[0095] S1, reed fiber treatment:

[0096] The reed fibers are placed in a soaking pool and soaked in a 1 wt% sodium hydroxide aqueous solution for 2 h at a temperature of 40℃. After soaking, the sodium hydroxide aqueous solution is filtered out, the reed fibers are washed with water until neutral, dried, and the water content is controlled to be 8%, to obtain purified reed fibers.

[0097] S2, wood chip treatment:

[0098] Put the wood chips into the steam treatment tank, and treat them in saturated steam at 180℃ and 0.8MPa for 5min to improve the flexibility and plasticity of the wood chips, and the moisture content of the treated wood chips is controlled at 6%, obtaining softened wood chips;

[0099] S3, premixing treatment:

[0100] Firstly, basalt fiber, nano-silicon dioxide, acetylated disaccharide phosphate, and methyl methacrylate cross-linked polymer are subjected to first airflow mixing with parameters of airflow speed 10m / s, pressure 0.4MPa, and mixing time 10min; then lignin fiber is added for second airflow mixing with parameters of airflow speed 8m / s, pressure 0.3MPa, and mixing time 5min, obtaining mixture A;

[0101] S4, glue mixing:

[0102] Purified reed fiber, softened wood chips, and plant extract are added into the glue mixer, and stirred at 300r / min for 2min to mix uniformly; then mixture A is added, and stirred at 600r / min for 5min to mix uniformly; then MDI adhesive and PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane cross-linked polymer are added in sequence under stirring, and stirred at 600r / min for 5min to mix uniformly; then C30-45 alkyl cetyl stearyl polydimethylsiloxane cross-linked polymer and silicone waterproof agent are added in sequence under stirring, and stirred at 500r / min for 3min to mix uniformly, obtaining the base material;

[0103] S5, paving and orientation:

[0104] The base material is paved through paving equipment, and according to the thickness requirement, 1cm, 1.5cm, 2cm, 2.5cm, 3cm, and 5cm paving thicknesses are implemented respectively, and mechanical orientation device is used to arrange the long axis direction of the softened wood chips at an angle of 45° with the length direction of the board to improve the mechanical properties of the board, and other components are uniformly distributed and filled between the softened wood chips, obtaining the paved and oriented board blank;

[0105] S6, hot pressing:

[0106] The paved and oriented board blank is sent into the continuous flat pressing hot press for continuous hot pressing with hot pressing speed 410mm / s, hot pressing factor 3.6s / mm, and heat medium being heat conducting oil; the continuous flat pressing hot press is divided into five zones from front to back, namely zone 1, zone 2, zone 3, zone 4, and zone 5, and the pressure and temperature settings of each zone are as follows:

[0107] Zone 1: system 1: 92N / cm 2 , system 2: 282N / cm 2 , temperature 237℃;

[0108] Zone 2: System 3: 422 N / cm 2 , System 4: 452 N / cm 2 , System 5: 377 N / cm 2 , System 6: 337 N / cm 2 , System 7: 282 N / cm 2 , System 8: 242 N / cm 2 , System 9: 212 N / cm 2 , Temperature 237℃;

[0109] Zone 3: System 10: 152 N / cm 2 , System 11: 142 N / cm 2 , System 12: 132 N / cm 2 , Temperature 232℃;

[0110] Zone 4: System 13: 92 N / cm 2 , System 14: 132 N / cm 2 , System 15: 132 N / cm 2 , System 16: 92 N / cm 2 , System 17: 132 N / cm 2 , System 18: 132 N / cm 2 , System 19: 132 N / cm 2 , System 20: 132 N / cm 2 , Temperature 202℃;

[0111] Zone 5: System 21: 52 N / cm 2 , Temperature 192℃.

[0112] After continuous hot pressing, a hot-pressed board is obtained.

[0113] S7, post-processing:

[0114] The hot-pressed board is cooled by air cooling to room temperature, and then edge cutting and sanding are performed to make the board size accurate and the surface flat, and different thicknesses of reed-wood composite particle boards are obtained.

[0115] Select 1.5 cm thick reed-wood composite particle board as a test sample.

[0116] Example 3

[0117] An environmentally friendly, deformation-resistant reed-wood composite particleboard comprises the following raw materials in parts by weight: 70 parts wood chips, 60 parts reed fiber, 5 parts basalt fiber, 5 parts lignin fiber, 0.5 parts plant extract, 5 parts nano silica, 1 part acetylated distarch phosphate, 5 parts C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer, 1 part PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer, 6 parts methyl methacrylate crosslinking polymer, 6 parts MDI adhesive, and 1 part silicone waterproofing agent.

[0118] The wood chips are oak tree trunk chips. The specifications of the wood chips are: length range 5cm–8cm, width range 0.5cm–2cm, and thickness range 0.2cm–0.5cm. The specifications of the reed fiber are: length range 2cm–4cm, width range 0.1cm–0.5cm, and thickness range 0.1cm–0.3cm. The specifications of the basalt fiber are: length range 0.3cm–0.8cm, and diameter range 5μm–15μm. The lignin fiber is flocculent lignin fiber, with a length range of less than 0.6cm. The particle size of the nano-silica is less than 300nm. The particle size of the acetylated distarch phosphate is passing through a 250-mesh sieve. The particle size of the methyl methacrylate cross-linked polymer is passing through a 250-mesh sieve.

[0119] The preparation method of the plant extract includes the following steps: Artemisia argyi: Pyrethrum sylvestris: Echinacea purpurea: Rosemary are mixed in a mass ratio of 5:10:5:3. The whole plants of Artemisia argyi, Pyrethrum sylvestris, Echinacea purpurea and Rosemary are mixed and crushed to obtain a pulverized material. Then, the pulverized material is percolated with 8 times its mass of ethanol to obtain an extract. The ethanol is evaporated to remove the ethanol, and the extract is dried and dispersed to obtain the plant extract.

[0120] The preparation method of the above-mentioned environmentally friendly and deformation-resistant reed-wood composite particleboard includes the following steps:

[0121] S1, Reed fiber treatment:

[0122] The reed fiber was placed in a soaking tank and soaked in a 2wt% sodium hydroxide aqueous solution for 2 hours. The soaking temperature was controlled at 50℃. After soaking, the sodium hydroxide aqueous solution was filtered out. The reed fiber was rinsed with clean water until neutral and dried to control the moisture content at 8% to obtain purified reed fiber.

[0123] S2: Wood chip processing:

[0124] Wood chips are placed in a steam treatment tank and treated in saturated steam at 200°C and 0.8MPa for 10 minutes to improve the flexibility and plasticity of the wood chips. The moisture content of the treated wood chips is controlled at 6%, resulting in softened wood chips.

[0125] S3, Premixing treatment:

[0126] Basalt fiber, nano-silica, acetylated distarch phosphate, and methyl methacrylate crosslinked polymer were subjected to a first airflow mixing with parameters of 20 m / s airflow velocity, 0.4 MPa pressure, and 15 min mixing time. Then, lignin fiber was added, and a second airflow mixing was performed with parameters of 8 m / s airflow velocity, 0.5 MPa pressure, and 5 min mixing time to obtain mixture A.

[0127] S4, Mixing adhesive:

[0128] Purified reed fiber, softened wood chips, and plant extracts were added to a mixer and stirred at 500 rpm for 2 minutes until homogeneous. Then, mixture A was added and stirred at 700 rpm for 5 minutes until homogeneous. Next, while stirring, MDI adhesive and PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer were added sequentially and stirred at 700 rpm for 5 minutes until homogeneous. Finally, while stirring, C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer and silicone waterproofing agent were added sequentially and stirred at 600 rpm for 3 minutes until homogeneous, thus obtaining the base material.

[0129] S5, Paving and Orientation:

[0130] The base material is laid using a laying equipment. Depending on the thickness requirements, laying thicknesses of 1cm, 1.5cm, 2cm, 2.5cm, 3cm, and 5cm are applied. A mechanical orientation device is used to align the long axis of the softened wood chips at a 45° angle to the length of the board to improve the mechanical properties of the board. Other components are evenly distributed and filled between the softened wood chips to obtain the laid and oriented board blank.

[0131] S6, Hot pressing:

[0132] The oriented slabs are fed into a continuous flat-press hot press for continuous hot pressing: the hot pressing speed is 750 mm / s, the hot pressing factor is 4.2 s / mm, and the heat transfer medium is heat transfer oil; the continuous flat-press hot press is divided into five zones from front to back, namely zone one, zone two, zone three, zone four, and zone five, with the following pressure and temperature settings for each zone:

[0133] Zone 1: System 1: 88 N / cm 2 System 2: 278 N / cm 2 Temperature 232℃;

[0134] Zone 2: System 3: 418 N / cm 2 System 4: 448 N / cm 2 System 5: 372 N / cm 2System 6: 332 N / cm 2 System 7: 278 N / cm 2 System 8: 238 N / cm 2 System 9: 208 N / cm 2 Temperature 232℃;

[0135] Zone 3: System 10: 148 N / cm 2 System 11: 138 N / cm 2 System 12: 128 N / cm 2 Temperature 228℃;

[0136] Zone 4: System 13: 88 N / cm 2 System 14: 128 N / cm 2 System 15: 128 N / cm 2 System 16: 88 N / cm 2 System 17: 128 N / cm 2 System 18: 128 N / cm 2 System 19: 128 N / cm 2 System 20: 128 N / cm 2 Temperature 198℃;

[0137] Zone 5: System 21: 48 N / cm 2 The temperature is 188℃.

[0138] After continuous hot pressing, a hot-pressed sheet is obtained;

[0139] S7, Post-processing:

[0140] After hot pressing, the boards are cooled naturally to room temperature. Then, the boards are trimmed and sanded to ensure accurate dimensions and a smooth surface, resulting in reed composite particleboard of different thicknesses.

[0141] A 1.5cm thick layer of reed-wood composite particleboard was selected as the test sample.

[0142] Example 4

[0143] An environmentally friendly, deformation-resistant reed-wood composite particleboard comprises the following raw materials in parts by weight: 60 parts wood chips, 50 parts reed fiber, 10 parts basalt fiber, 5 parts lignin fiber, 1 part plant extract, 5 parts nano silica, 4 parts acetylated distarch phosphate, 5 parts C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer, 3 parts PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer, 6 parts methyl methacrylate crosslinking polymer, 8 parts MDI adhesive, and 1 part silicone waterproofing agent.

[0144] The wood chips are oak tree trunk chips. The specifications of the wood chips are: length range 5cm–8cm, width range 0.5cm–2cm, and thickness range 0.2cm–0.5cm. The specifications of the reed fiber are: length range 2cm–4cm, width range 0.1cm–0.5cm, and thickness range 0.1cm–0.3cm. The specifications of the basalt fiber are: length range 0.3cm–0.8cm, and diameter range 5μm–15μm. The lignin fiber is flocculent lignin fiber, with a length range of less than 0.6cm. The particle size of the nano-silica is less than 300nm. The particle size of the acetylated distarch phosphate is passing through a 250-mesh sieve. The particle size of the methyl methacrylate cross-linked polymer is passing through a 250-mesh sieve.

[0145] The preparation method of the plant extract includes the following steps: Artemisia argyi: Pyrethrum sylvestris: Echinacea purpurea: Rosemary are mixed in a mass ratio of 10:10:10:3. The whole plants of Artemisia argyi, Pyrethrum sylvestris, Echinacea purpurea and Rosemary are mixed, pulverized, and then percolated with 10 times the mass of ethanol to obtain an extract. The ethanol is evaporated to remove the extract, and after drying and dispersing, the plant extract is obtained.

[0146] The preparation method of the above-mentioned environmentally friendly and deformation-resistant reed-wood composite particleboard includes the following steps:

[0147] S1, Reed fiber treatment:

[0148] The reed fiber was placed in a soaking tank and soaked in a 2wt% sodium hydroxide aqueous solution for 3 hours. The soaking temperature was controlled at 50℃. After soaking, the sodium hydroxide aqueous solution was filtered out. The reed fiber was rinsed with clean water until neutral and dried to control the moisture content at 12% to obtain purified reed fiber.

[0149] S2: Wood chip processing:

[0150] Wood chips are placed in a steam treatment tank and treated in saturated steam at 200°C and 1.2 MPa for 10 minutes to improve the flexibility and plasticity of the wood chips. The moisture content of the treated wood chips is controlled at 10%, resulting in softened wood chips.

[0151] S3, Premixing treatment:

[0152] Basalt fiber, nano-silica, acetylated distarch phosphate, and methyl methacrylate crosslinked polymer were subjected to a first airflow mixing with parameters of 20 m / s airflow velocity, 0.6 MPa pressure, and 15 min mixing time. Then, lignin fiber was added, and a second airflow mixing was performed with parameters of 15 m / s airflow velocity, 0.5 MPa pressure, and 10 min mixing time to obtain mixture A.

[0153] S4, Mixing adhesive:

[0154] Purified reed fiber, softened wood chips, and plant extracts were added to a mixer and stirred at 500 rpm for 3 minutes until homogeneous. Then, mixture A was added and stirred at 700 rpm for 8 minutes until homogeneous. Next, while stirring, MDI adhesive and PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer were added sequentially and stirred at 700 rpm for 8 minutes until homogeneous. Finally, while stirring, C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer and silicone waterproofing agent were added sequentially and stirred at 600 rpm for 5 minutes until homogeneous, thus obtaining the base material.

[0155] S5, Paving and Orientation:

[0156] The base material is laid using a laying equipment. Depending on the thickness requirements, laying thicknesses of 1cm, 1.5cm, 2cm, 2.5cm, 3cm, and 5cm are applied. A mechanical orientation device is used to align the long axis of the softened wood chips at a 60° angle to the length of the board to improve the mechanical properties of the board. Other components are evenly distributed and filled between the softened wood chips to obtain the laid and oriented board blank.

[0157] S6, Hot pressing:

[0158] The oriented slabs are fed into a continuous flat-press hot press for continuous hot pressing: the hot pressing speed is 350 mm / s, the hot pressing factor is 3.3 s / mm, and the heat transfer medium is heat transfer oil; the continuous flat-press hot press is divided into five zones from front to back, namely zone one, zone two, zone three, zone four, and zone five, with the following pressure and temperature settings for each zone:

[0159] Zone 1: System 1: 85 N / cm 2 System 2: 275 N / cm 2 Temperature 230℃;

[0160] Zone 2: System 3: 415 N / cm 2 System 4: 445 N / cm 2 System 5: 370 N / cm 2 System 6: 330 N / cm 2 System 7: 275 N / cm 2 System 8: 235 N / cm 2 System 9: 205 N / cm 2 Temperature 230℃;

[0161] Zone 3: System 10: 145 N / cm 2 System 11: 135 N / cm2 System 12: 125 N / cm 2 Temperature 225℃;

[0162] Zone 4: System 13: 85 N / cm 2 System 14: 125 N / cm 2 System 15: 125 N / cm 2 System 16: 85 N / cm 2 System 17: 125 N / cm 2 System 18: 125 N / cm 2 System 19: 125 N / cm 2 System 20: 125 N / cm 2 Temperature 195℃;

[0163] Zone 5: System 21: 45 N / cm 2 The temperature is 185℃.

[0164] After continuous hot pressing, a hot-pressed sheet is obtained;

[0165] S7, Post-processing:

[0166] After hot pressing, the boards are cooled using air cooling to bring the temperature down to room temperature. Then, the boards are trimmed and sanded to ensure accurate dimensions and a smooth surface, resulting in reed-wood composite particleboard of different thicknesses.

[0167] A 1.5cm thick layer of reed-wood composite particleboard was selected as the test sample.

[0168] Example 5

[0169] An environmentally friendly, deformation-resistant reed-wood composite particleboard comprises the following raw materials in parts by weight: 60 parts wood chips, 55 parts reed fiber, 10 parts basalt fiber, 2 parts lignin fiber, 1 part plant extract, 2 parts nano silica, 4 parts acetylated distarch phosphate, 2 parts C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer, 3 parts PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer, 3 parts methyl methacrylate crosslinking polymer, 8 parts MDI adhesive, and 0.5 parts silicone waterproofing agent.

[0170] The wood chips are oak tree trunk chips. The specifications of the wood chips are: length range 5cm–8cm, width range 0.5cm–2cm, and thickness range 0.2cm–0.5cm. The specifications of the reed fiber are: length range 2cm–4cm, width range 0.1cm–0.5cm, and thickness range 0.1cm–0.3cm. The specifications of the basalt fiber are: length range 0.3cm–0.8cm, and diameter range 5μm–15μm. The lignin fiber is flocculent lignin fiber, with a length range of less than 0.6cm. The particle size of the nano-silica is less than 300nm. The particle size of the acetylated distarch phosphate is passing through a 250-mesh sieve. The particle size of the methyl methacrylate cross-linked polymer is passing through a 250-mesh sieve.

[0171] The preparation method of the plant extract includes the following steps: Artemisia argyi: Pyrethrum sylvestris: Echinacea purpurea: Rosemary are mixed in a mass ratio of 10:5:7:5. The whole plants of Artemisia argyi, Pyrethrum sylvestris, Echinacea purpurea and Rosemary are mixed, pulverized, and then percolated with 10 times the mass of ethanol to obtain an extract. The ethanol is evaporated to remove the extract, and after drying and dispersing, the plant extract is obtained.

[0172] The preparation method of the above-mentioned environmentally friendly and deformation-resistant reed-wood composite particleboard includes the following steps:

[0173] S1, Reed fiber treatment:

[0174] The reed fiber was placed in a soaking tank and soaked in a 1 wt% sodium hydroxide aqueous solution for 3 hours. The soaking temperature was controlled at 40℃. After soaking, the sodium hydroxide aqueous solution was filtered out. The reed fiber was rinsed with clean water until neutral and dried to control the moisture content at 12% to obtain purified reed fiber.

[0175] S2: Wood chip processing:

[0176] Wood chips are placed in a steam treatment tank and treated in saturated steam at 180°C and 1.2 MPa for 5 minutes to improve the flexibility and plasticity of the wood chips. The moisture content of the treated wood chips is controlled at 10%, resulting in softened wood chips.

[0177] S3, Premixing treatment:

[0178] Basalt fiber, nano-silica, acetylated distarch phosphate, and methyl methacrylate crosslinked polymer were subjected to a first airflow mixing with parameters of 10 m / s airflow velocity, 0.6 MPa pressure, and 10 min mixing time. Then, lignin fiber was added, and a second airflow mixing was performed with parameters of 15 m / s airflow velocity, 0.3 MPa pressure, and 10 min mixing time to obtain mixture A.

[0179] S4, Mixing adhesive:

[0180] Purified reed fiber, softened wood chips, and plant extracts were added to a mixer and stirred at 300 rpm for 3 minutes until homogeneous. Then, mixture A was added and stirred at 600 rpm for 8 minutes until homogeneous. Next, while stirring, MDI adhesive and PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer were added sequentially and stirred at 600 rpm for 8 minutes until homogeneous. Finally, while stirring, C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer and silicone waterproofing agent were added sequentially and stirred at 500 rpm for 5 minutes until homogeneous, thus obtaining the base material.

[0181] S5, Paving and Orientation:

[0182] The base material is laid using a laying equipment. Depending on the thickness requirements, laying thicknesses of 1cm, 1.5cm, 2cm, 2.5cm, 3cm, and 5cm are applied. A mechanical orientation device is used to align the long axis of the softened wood chips at a 60° angle to the length of the board to improve the mechanical properties of the board. Other components are evenly distributed and filled between the softened wood chips to obtain the laid and oriented board blank.

[0183] S6, Hot pressing:

[0184] The oriented slabs are fed into a continuous flat-press hot press for continuous hot pressing: the hot pressing speed is 580 mm / s, the hot pressing factor is 4.5 s / mm, and the heat transfer medium is heat transfer oil; the continuous flat-press hot press is divided into five zones from front to back, namely zone one, zone two, zone three, zone four, and zone five, with the following pressure and temperature settings for each zone:

[0185] Zone 1: System 1: 95 N / cm 2 System 2: 285 N / cm 2 Temperature 240℃;

[0186] Zone 2: System 3: 425 N / cm 2 System 4: 455 N / cm 2 System 5: 380 N / cm 2 System 6: 340 N / cm 2 System 7: 285 N / cm 2 System 8: 245 N / cm 2 System 9: 215 N / cm 2 Temperature 240℃;

[0187] Zone 3: System 10: 155 N / cm 2 System 11: 145 N / cm 2 System 12: 135 N / cm2 Temperature 235℃;

[0188] Zone 4: System 13: 95 N / cm 2 System 14: 135 N / cm 2 System 15: 135 N / cm 2 System 16: 95 N / cm 2 System 17: 135 N / cm 2 System 18: 135 N / cm 2 System 19: 135 N / cm 2 System 20: 135 N / cm 2 Temperature 205℃;

[0189] Zone 5: System 21: 55 N / cm 2 The temperature is 195℃.

[0190] After continuous hot pressing, a hot-pressed sheet is obtained;

[0191] S7, Post-processing:

[0192] After hot pressing, the boards are cooled using air cooling to bring the temperature down to room temperature. Then, the boards are trimmed and sanded to ensure accurate dimensions and a smooth surface, resulting in reed-wood composite particleboard of different thicknesses.

[0193] A 1.5cm thick layer of reed-wood composite particleboard was selected as the test sample.

[0194] The acetylated distarch phosphate used in the above embodiments was sourced from Shandong Kuoyi Biotechnology Co., Ltd. The C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer was sourced from Shaanxi Panier Biotechnology Co., Ltd. The PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer was sourced from Aoke New Materials Technology (Shanghai) Co., Ltd. The methyl methacrylate crosslinking polymer was sourced from Hubei Shishun Biotechnology Co., Ltd. The MDI adhesive, model MDI-50, was sourced from Wanhua Chemical. The silicone waterproofing agent was sourced from Shanghai Sangjing Chemical Co., Ltd.

[0195] Comparative Example 1

[0196] Basalt fiber was not added to the reed-wood composite particleboard, and other parameters and methods were the same as in Example 1; a 1.5 cm thick reed-wood composite particleboard was prepared as a test sample.

[0197] Comparative Example 2

[0198] No lignin fiber was added to the reed-wood composite particleboard, and other parameters and methods were the same as in Example 1; a 1.5 cm thick reed-wood composite particleboard was prepared as a test sample.

[0199] Comparative Example 3

[0200] The reed-wood composite particleboard was prepared without the addition of basalt fiber and lignin fiber, and the other parameters and methods were the same as in Example 1. A 1.5 cm thick reed-wood composite particleboard was prepared as a test sample.

[0201] Comparative Example 4

[0202] No nano-silica was added to the reed-wood composite particleboard, and other parameters and methods were the same as in Example 1; a 1.5 cm thick reed-wood composite particleboard was prepared as a test sample.

[0203] Comparative Example 5

[0204] No methyl methacrylate crosslinking polymer was added to the reed-wood composite particleboard, and other parameters and methods were the same as in Example 1; a 1.5 cm thick reed-wood composite particleboard was prepared as a test sample.

[0205] Comparative Example 6

[0206] The reed-wood composite particleboard was prepared without the addition of nano-silica and methyl methacrylate crosslinking polymer, and other parameters and methods were the same as in Example 1; a 1.5 cm thick reed-wood composite particleboard was prepared as a test sample.

[0207] Comparative Example 7

[0208] The reed-wood composite particleboard was not mixed with C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer, and other parameters and methods were the same as in Example 1; a 1.5 cm thick reed-wood composite particleboard was prepared as a test sample.

[0209] Comparative Example 8

[0210] The reed-wood composite particleboard was prepared without the addition of PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer, and other parameters and methods were the same as in Example 1; a 1.5 cm thick reed-wood composite particleboard was prepared as a test sample.

[0211] Comparative Example 9

[0212] The reed-wood composite particleboard was prepared without the addition of C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer and PE G-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer, and other parameters and methods were the same as in Example 1; a 1.5 cm thick reed-wood composite particleboard was prepared as a test sample.

[0213] Comparative Example 10

[0214] The reed-wood composite particleboard was prepared without the addition of nano-silica, methyl methacrylate cross-linked polymer, C30-45 alkyl cetearyl polydimethylsiloxane cross-linked polymer and PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane cross-linked polymer, and other parameters and methods were the same as in Example 1; a reed-wood composite particleboard with a laying thickness of 1.5 cm was prepared as a test sample.

[0215] Comparative Example 11

[0216] In the preparation method, S4, mixing the adhesive: the purified reed fiber, softened wood chips, plant extracts, mixture A, MDI adhesive, PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer, C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer and organosilicon waterproofing agent are added to the adhesive mixer and stirred at 650 r / min for 20 min to obtain the base material; other parameters and methods are the same as in Example 1; a reed-wood composite particleboard with a laying thickness of 1.5 cm is prepared as a test sample.

[0217] Comparative Example 12

[0218] In step S6 of the preparation method, the pressure and temperature of each zone are set to constant temperature and constant pressure: hot pressing temperature 235℃, pressure 450N / cm. 2 The hot-pressed board was obtained; other parameters and methods were the same as in Example 1; a 1.5cm thick reed-wood composite particleboard was prepared as a test sample.

[0219] Comparative Example 13

[0220] No plant extracts were added to the reed-wood composite particleboard, and other parameters and methods were the same as in Example 1; a 1.5cm thick reed-wood composite particleboard was prepared as a test sample.

[0221] Comparative Example 14

[0222] Plant extracts were prepared separately, without preparing boards; Echinacea was not added to the raw materials for the plant extracts, and other preparation methods and parameters for the plant extracts were the same as in Example 1.

[0223] Comparative Example 15

[0224] Plant extracts were prepared separately, without preparing boards; rosemary was not added to the raw materials of the plant extracts, and other preparation methods and parameters of the plant extracts were the same as in Example 1.

[0225] Comparative Example 16

[0226] Plant extracts were prepared separately, without preparing boards; echinacea and rosemary were not added to the raw materials for the plant extracts; other preparation methods and parameters for the plant extracts were the same as in Example 1.

[0227] 1. Performance testing was conducted on the plates of the above embodiments and Comparative Examples 1 to 12.

[0228] According to the following standard documents: GB / T 17657, GB / T 4897, GB 18580.

[0229] 1. Static bending strength test: A 200mm long and 50mm wide board specimen was placed on two supports of a computer-controlled artificial board testing machine. The support span was 150mm. A concentrated load was applied at the midpoint of the span at a loading speed of 10mm / min until the specimen failed. The maximum load and mid-span deflection were recorded. The static bending strength was calculated using the formula: σ=3PL / 2bh2 (where σ is the static bending strength, P is the failure load, L is the span, b is the specimen width, and h is the specimen thickness). The results are shown in Table 1 below.

[0230] 2. Internal bond strength test: Place a 50mm×50mm plate sample into a special instrument, apply a tensile force perpendicular to the plate surface through a suitable clamp, with a loading speed of about 5mm / min, until the sample breaks, and record the maximum tensile force as the internal bond strength; the results are shown in Table 1 below.

[0231] 3. Screw holding force test: Take a plate sample with a length of 150mm and a width of 50mm, pre-drill holes in the sample, screw in an M5×20 screw, and then use a special screw holding force test device to pull the screw out of the plate at a speed of 5mm / min. Record the maximum pull-out force as the screw holding force. The results are shown in Table 1 below.

[0232] 4. Crack resistance test: A square plate sample with a side length of 20cm was cut and fixed on the holder. The bending test machine was used with the three-point bending method. The loading speed was set to 5mm / min and the span was set to 160mm. The test was started and the loading force was gradually increased until visible cracks appeared on the sample. The maximum loading force was recorded. The bearing capacity results are shown in Table 1 below.

[0233] 5. Water absorption and swelling deformation test: Immerse a 100mm long and 100mm wide board sample in water for 24 hours, observe the deformation after water absorption and swelling, measure the dimensional changes before and after immersion, and calculate the water absorption and swelling rate. Water absorption and swelling rate = (dimensional changes after immersion - dimensional changes before immersion) / dimensional changes before immersion × 100%.

[0234] 6. Formaldehyde Emission Detection: Using the climate chamber method, the board samples from Examples 1 to 5 were placed in a climate chamber and the amount of formaldehyde released within 24 hours was measured under specified conditions of 40°C and 35% humidity. The test results showed that no formaldehyde was detected.

[0235] Table 1. Test Results of Sheet Material Performance

[0236]

[0237] The results above show that the boards from Examples 1 to 5 possess excellent mechanical properties, strong crack resistance, strong deformation resistance, and more stable board quality. The results from Comparative Examples 1 to 3 show that the absence of basalt fiber or lignin fiber leads to a corresponding decrease in various properties; the absence of both basalt fiber and lignin fiber results in a significant decrease in various properties. The results from Comparative Examples 4 to 6 show that the absence of nano-silica or methyl methacrylate cross-linked polymer leads to a corresponding decrease in various properties; the absence of both nano-silica and methyl methacrylate cross-linked polymer results in a significant decrease in various properties. The results of Comparative Examples 7 to 9 show that without the addition of C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer or PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer, various properties decrease accordingly, especially water absorption, leading to an increased deformation rate. Simultaneously, without both C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer and PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer, water absorption and expansion deformation rate increase significantly. The results of Comparative Example 10 show that without the addition of nano-silica, methyl methacrylate crosslinking polymer, C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer, and PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer in the reed composite particleboard, various properties decrease significantly. The results of Comparative Example 11 show that changing the mixing method leads to poor homogeneity of the board, unstable properties, and worsened indicators. The results of Comparative Example 12 show that the design of the pressure and temperature parameters during hot pressing affects the stability of the pressed board quality, and suitable hot pressing parameters can improve various properties of the board. The results of Comparative Example 13 show that the absence of plant extracts in reed-wood composite particleboard has little impact on the mechanical properties and water absorption of the board.

[0238] 2. The plant extracts of Examples 1 to 5 and the plant extracts of Comparative Examples 13 to 15 were tested for antibacterial and insect-repellent properties.

[0239] 1. Antibacterial test: First, the test bacterial solution was evenly spread on a sterilized agar medium plate. Then, Oxford cups were placed on the plate, and an appropriate amount of plant extract solution was added to the Oxford cups. After incubation at a suitable temperature for a certain period of time for each strain, the size of the inhibition zone was observed and measured. The larger the inhibition zone, the stronger the antibacterial effect. Strains: Escherichia coli, Staphylococcus aureus, and mold. The test results are shown in Table 2 below.

[0240] 2. Insect Repellency Test: The plant extract was diluted with pure water to a 10-fold mass ratio to obtain a plant extract solution. A portion of filter paper was soaked in the plant extract solution and then dried to obtain treated filter paper. A portion of filter paper was left untreated. Multiple areas were set up, with some areas containing treated filter paper and others containing untreated filter paper. Fifty ants, 20 silver beetles, and 10 cockroaches were placed in this environment, and the insects' attraction to different materials and the degree of damage were observed to determine the insect repellency performance of the plant extract. The test results are shown in Table 2 below.

[0241] Table 2 Results of antibacterial and insect-repellent tests

[0242]

[0243]

[0244] The results above indicate that the combined use of mugwort, white pyrethrum, echinacea, and rosemary exhibits good antibacterial and insecticidal effects. Echinacea and rosemary demonstrate a strong synergistic effect in inhibiting bacterial strains.

[0245] III. Evaluation of the storage resistance to mold and insects of the sample plates from Example 1 and Comparative Example 13:

[0246] The boards from Example 1 and Comparative Example 13 were stored in a dark and humid environment at 30°C and 65% humidity for 14 days, and the mold and insect infestation were observed. Results: The board from Example 1 showed almost no mold or insect infestation; the board from Comparative Example 13 showed obvious mold and insect infestation.

Claims

1. A method for preparing an environmentally friendly, deformation-resistant reed-wood composite particleboard, characterized in that, The preparation method includes the following steps: S1, Reed fiber treatment: The reed fiber was placed in a soaking tank and soaked in a sodium hydroxide solution. After soaking, the sodium hydroxide solution was filtered out. The reed fiber was rinsed with clean water until neutral and dried so that the moisture content was controlled at 8% to 12% to obtain purified reed fiber. S2: Wood chip processing: Wood chips are placed in a steam treatment tank and treated in saturated steam at 180℃~200℃ and 0.8MPa~1.2MPa for 5min~10min. The moisture content of the treated wood chips is controlled at 6%~10%, thus obtaining softened wood chips. S3, Premixing treatment: Basalt fiber, nano-silica, acetylated distarch phosphate, and methyl methacrylate crosslinked polymer were first air-mixed, and then lignin fiber was added and air-mixed a second time to obtain mixture A. S4, Mixing adhesive: Purified reed fiber, softened wood chips, and plant extracts were added to a mixing machine and stirred at 300-500 rpm for 2-3 minutes until homogeneous. Then, mixture A was added and stirred at 600-700 rpm for 5-8 minutes until homogeneous. Next, while stirring, MDI adhesive and PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer were added sequentially and stirred at 600-700 rpm for 5-8 minutes until homogeneous. Finally, while stirring, C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer and silicone waterproofing agent were added sequentially and stirred at 500-600 rpm for 3-5 minutes until homogeneous, yielding the base material. S5, Paving and Orientation: The base material is laid using a laying equipment, with the laying thickness controlled between 1cm and 5cm. A mechanical orientation device is used to align the long axis of the softened wood chips at an angle of 45° to 60° with the length of the board to improve the mechanical properties of the board. Other components are evenly distributed and filled between the softened wood chips to obtain the laid and oriented board blank. S6, Hot pressing: The oriented slab is fed into a continuous flat-press hot press for continuous hot pressing: the hot pressing speed is 350mm / s~580mm / s, the hot pressing factor is 3.3s / mm~4.5s / mm, and the heat medium is heat transfer oil; after continuous hot pressing, the hot-pressed board is obtained. S7, Post-processing: After hot pressing, the boards are cooled using natural or air cooling methods to bring the temperature down to room temperature. Then, the boards are trimmed and sanded to ensure accurate dimensions and a smooth surface, resulting in reed-wood composite particleboard. The preparation method of the plant extract includes the following steps: Artemisia argyi: Pyrethrum sylvestris: Echinacea purpurea: Rosemary are mixed in a mass ratio of (5-10): (5-10): (5-10): (1-5) with whole plants of Artemisia argyi, Pyrethrum sylvestris, Echinacea purpurea and Rosemary, pulverized to obtain pulverized material, and then percolated with 8-10 times the mass of ethanol to obtain an extract. The ethanol is evaporated to remove the extract, and after drying and dispersing, the plant extract is obtained.

2. The method for preparing an environmentally friendly, deformation-resistant reed-wood composite particleboard according to claim 1, characterized in that, In S1, the concentration of the sodium hydroxide aqueous solution is 1wt% to 2wt%; the soaking time is 2h to 3h; and the soaking temperature is controlled at 40℃ to 50℃.

3. The method for preparing an environmentally friendly, deformation-resistant reed-wood composite particleboard according to claim 1, characterized in that, In S3, the parameters for the first airflow mixing are: airflow velocity 10m / s~20m / s, pressure 0.4MPa~0.6MPa, and mixing time 10min~15min; the parameters for the second airflow mixing are: airflow velocity 8m / s~15m / s, pressure 0.3MPa~0.5MPa, and mixing time 5min~10min.

4. The method for preparing an environmentally friendly, deformation-resistant reed-wood composite particleboard according to claim 1, characterized in that, In S6, the continuous flat-pressure hot press is divided into five zones from front to back: Zone 1, Zone 2, Zone 3, Zone 4, and Zone 5. The pressure and temperature settings for each zone are as follows: Zone 1: System 1: 90±5 N / cm 2 System 2: 280±5 N / cm 2 Temperature 235±5℃; Zone 2: System 3: 420±5 N / cm 2 System 4: 450±5 N / cm 2 System 5: 375±5 N / cm 2 System 6: 335±5 N / cm 2 System 7: 280±5 N / cm 2 System 8: 240±5 N / cm 2 System 9: 210±5 N / cm 2 Temperature 235±5℃; Zone 3: System 10: 150±5N / cm 2 System 11: 140±5 N / cm 2 System 12: 130±5 N / cm 2 Temperature 230±5℃; Zone 4: System 13: 90±5N / cm 2 System 14: 130±5 N / cm 2 System 15: 130±5 N / cm 2 System 16: 90±5 N / cm 2 System 17: 130±5 N / cm 2 System 18: 130±5 N / cm 2 System 19: 130±5 N / cm 2 System 20: 130±5 N / cm 2 Temperature 200±5℃; Zone 5: System 21: 50±5 N / cm 2 The temperature is 190±5℃.

5. An environmentally friendly, deformation-resistant reed-wood composite particleboard, manufactured by the preparation method of the environmentally friendly, deformation-resistant reed-wood composite particleboard according to claim 1, characterized in that, The reed-wood composite particleboard comprises the following raw materials in parts by weight: 60-70 parts wood chips, 50-60 parts reed fiber, 5-10 parts basalt fiber, 2-5 parts lignin fiber, 0.5-1 part plant extract, 2-5 parts nano silica, 1-4 parts acetylated distarch phosphate, 2-5 parts C30-45 alkyl cetearyl polydimethylsiloxane crosslinking polymer, 1-3 parts PEG-10 polydimethylsiloxane-vinyl polydimethylsiloxane crosslinking polymer, 3-6 parts methyl methacrylate crosslinking polymer, 6-8 parts MDI adhesive, and 0.5-1 part silicone waterproofing agent.

6. The environmentally friendly, deformation-resistant reed-wood composite particleboard according to claim 5, characterized in that, The wood chips are oak tree trunk chips; the specifications of the wood chips are: length ranging from 5cm to 8cm, width ranging from 0.5cm to 2cm, and thickness ranging from 0.2cm to 0.5cm.

7. The environmentally friendly, deformation-resistant reed-wood composite particleboard according to claim 5, characterized in that, The specifications of the reed fiber are: length ranging from 2cm to 4cm, width ranging from 0.1cm to 0.5cm, and thickness ranging from 0.1cm to 0.3cm.

8. The environmentally friendly, deformation-resistant reed-wood composite particleboard according to claim 5, characterized in that, The specifications of the basalt fiber are: length range of 0.3cm to 0.8cm and diameter range of 5μm to 15μcm; the lignin fiber is flocculent lignin fiber, and the length range of the flocculent lignin fiber is less than 0.6cm.

9. The environmentally friendly, deformation-resistant reed-wood composite particleboard according to claim 5, characterized in that, The particle size of the nano-silica is below 300 nm; the particle size of the acetylated distarch phosphate is below a 250-mesh sieve; and the particle size of the methyl methacrylate cross-linked polymer is below a 250-mesh sieve.

Citation Information

Patent Citations

  • Vitrification materials to partial oxidation gasifier

    CA3174898A1

  • Basalt fiber reinforced wood-plastic composite material and preparation method thereof

    CN101906250A